Determinants of Non-performing Loans-The Role of Cost Efficiency - Li, Jun (2019)
This paper investigates whether the cost efficiency score can be one of the factors explaining non-performing loans in the US banking industry. Most literatures based on this topic utilise data from the Eurozone, and a few articles about the US banking system use the cost-to-income ratio instead of the efficiency score obtained from the efficient frontier. By using the data set of top 100 commercial banks in the United States during the period 2011-2018, this paper utilises the Stochastic Frontier Analysis to measure the cost efficiency score. The results exhibit the mean cost efficiency score for all estimated years, which is 92.75%, ranging from 32.34% to 99.63%. Following this, by applying the Generalised Moment Method, it estimates the determinants of non-performing loans. This paper tests the primary hypothesis called as bad management or skimping, which reflects the relationship between cost efficiency and impaired loans. Besides, it assesses other traditional hypotheses including bad management II or procyclical credit policy, moral hazard, credit quality, bank size, business cycle and life cycle. According to the results, it can be found that the cost efficiency score has a significantly negative relationship with NPLs. Besides, capitalisation has negative influences on NPLs, while there is a positive relationship between loan loss reserves and NPL. Moreover, GDP growth rate has a negative effect on NPLs while the unemployment rate is positively associated with NPLs.